Acinic Cell Carcinoma of Salivary Gland – Report of a Case - Iqbal, Sana (International Journal of Pathology, 2021)
Introduction: Acinic cell carcinoma is a rare salivary gland tumor most commonly occurring in the parotid gland of the elderly female. It use to be often referred to as acinic cell tumor but follow ups revealed that in most cases it behaved as a malignant tumor. The cytological atypia is minimal and hence not a reliable criteria for prognosis. All acinic cell tumors should be handled as potentially malignant tumors.Report of a Case: We report a case of a sixty years old man who suffered from acinic cell carcinoma of the parotid gland that presented as a 5x5 cm painless lump developed over 8 years. It extended from the tragus of the left ear to the angle of mandible with intact facial nerve function. The lump became painful when the patient lied down facing the left side of the face. After CT scan the patient underwent surgery. The biopsy revealed acinic cell carcinoma.Conclusions: High index of suspicion for malignancy is required to diagnose acinic cell carcinoma and its follow up.